1977
DOI: 10.1002/bjs.1800641113
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal repair in chronic venous ulcers

Abstract: Certain features of epidermal repair, namely increased mitotic activity, cell migration and cell differentiation, have been investigated in fresh biopsies from 17 patients with chronic venous ulcers, using light and electron microscopy. Increased mitotic activity was present at the edges of most of these lesions whether they were in a grossly recognizable healing or non-healing phase, and some cells with ultrastructural features of migratory cells were invariably seen. The results are discussed in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The dermal-epidermal junction takes on a very convoluted appearance, with prominent rete ridges, and substantial vascular ingrowth, which takes on a glomerular appearance, into the dermal papillae. [102][103][104] Galkowska et al 105 reported that keratinocyte and dermal vascular endothelial cell capacities remain unimpaired in the margin of chronic venous ulcer, as determined by the expression of growth factors and cytokines at generally a higher level than more distant skin. Andriessen et al 104 showed by immunolocalization of cell proliferation antigens that wound edge keratinocyte proliferation remains unimpaired.…”
Section: Characteristics Of Peri-ulcer Tissuementioning
confidence: 99%
“…The dermal-epidermal junction takes on a very convoluted appearance, with prominent rete ridges, and substantial vascular ingrowth, which takes on a glomerular appearance, into the dermal papillae. [102][103][104] Galkowska et al 105 reported that keratinocyte and dermal vascular endothelial cell capacities remain unimpaired in the margin of chronic venous ulcer, as determined by the expression of growth factors and cytokines at generally a higher level than more distant skin. Andriessen et al 104 showed by immunolocalization of cell proliferation antigens that wound edge keratinocyte proliferation remains unimpaired.…”
Section: Characteristics Of Peri-ulcer Tissuementioning
confidence: 99%
“…So called ''non-healing'' ulcers, such as diabetic, venous, and pressure ulcers, are still challenging problems for clinicians [9,10]. Although many treatments, including reconstructive surgery and wound application, have succeeded in reducing the number of such patients, many still have incurable ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…They can be defined as a wound that is not continuously progressing toward healing 9 or not healing in a methodical and timely fashion 8 . Pathologically, one of the clearest indicators of a chronic wound is their failure to re-epithelialize 10 . The aging population are among those most burdened with chronic wounds, and with low keratinocyte cell turnover, this is a factor affecting their ability to re-epithelialize 11 .…”
Section: Main Textmentioning
confidence: 99%